A Practically Modified Approach With Complete Posterior Mobilization for Three-port Sleeve Gastrectomy: Single-center Experience. Issue 5 (9th October 2022) - Pan, Hsin-Mei; Liao, Guo-Shiou; Lin, Chien-Hua; Feng, Ting-Yuan; Hsu, Fang-Chin; Chang, Po-Chih; Hsu, Kuo-Feng
Abstract : Background: Although the procedure of laparoscopic sleeve gastrectomy (LSG) has been standardized either in conventional lateral to medial or medial to lateral approach, surgeons occasionally face the challenge of poor visualization of the His angle and difficulty in complete posterior mobilization in limited surgical field. This study aimed to introduce our novel details of modified approach to address these issues. Methods: One hundred patients with obesity underwent modified approach- three-port laparoscopic sleeve gastrectomy. Herein, we demonstrated our method to ease the procedure of gastric fundus mobilization with extensive posterior mobilization (shown in video, Supplemental Digital Content 1, http://links.lww.com/SLE/A336 ). The demographic characteristics and perioperative data were reviewed. Results: There was no case of conversion to open surgery. The mean operative time, volume of blood loss, and hospital stay were 72.5±22.7 minutes, 11.6±10.5 mL, and 4.3±2.1 days, respectively. One postoperative leakage was observed and it was successfully treated with metallic covered stent. The percentage of total weight loss at 6 months and 1 year were 20.3±8.4 and 29.8±9.2, respectively. Conclusions: Our experience showed that the modified technique is feasible and may help surgeons to accomplish a complete posterior mobilization, and better address the poor visualization of the the His angle-site owing to the interposition of floating omentum or bulging part of the stomach.